KOMPARASI PEMIKIRAN PENDIDIKAN ISLAM ABU HAMID AL-GHAZALI DAN MUHAMMAD ABDUH TENTANG MORAL PESERTA DIDIK - Subaidi Subaidi; Mardiyah Mardiyah; Muhammad Yusron Maulana El-Yunusi (STAI Ma'had Aly Al-Hikam Malang, 2022)
This research is literature research or library research that reveals the thoughts of al-Ghazali and Muhammad Abduh about the morals of students. The method used in collecting data in writing this thesis is the documentation method. Some of the data collected include primary data in the form of Islamic education thoughts by al-Ghazali and Muhammad Abduh about the morals of students and secondary data in the form of writings that try to discuss the thoughts of Islamic education by al-Ghazali and Muhammad Abduh about student morals and literature. -literature relevant to this study. The similarity of thoughts of al-Ghazali and Muhammad Abduh regarding education is that education is a human means to achieve happiness in the world and the hereafter and is oriented towards the formation of humans as complete human beings, both in this world and in the hereafter. The moral ideal criteria that must be possessed by a student regarding the student's relationship with his God in the view of al-Ghazali and Muhammad Abduh is that he must have commendable qualities, such as holy intentions in studying for Allah, piety, humility, focus on learning. by avoiding worldly dependence and tawakkal.